STRATEGI PENGEMBANGAN WATER SPORT DI PANTAI TANJUNG AAN KABUPATEN LOMBOK TENGAH, NUSA TENGGARA BARAT - Susi Kurniawati; I Putu Anom; I Nyoman Sukma Arida (JURNAL MASTER PARIWISATA, 2023)
The purpose of this study is to ascertain the potential for developing water sports on Tanjung Aan Beach and how the role of stakeholders is as well as how alternative strategies for developing water sports on Tanjung Aan Beach are. The qualitative method was used in this study. In this study, primary and secondary data were collected through focus group discussions (FGD), interviews, observations, and documentation with informants including ITDC, Sengkol Village Head, Pokdarwis Chair, HPI Central Lombok Chair, Chairperson Central Lombok PSOI, Tanjung Aan Beach Business Actors, Community and Fishermen. The SWOT analysis method was used to analyze the data in this study. This study answers the results of the three formulations of the problem, namely Tanjung Aan Beach has the potential for natural, cultural, and artificial tourism. The nature that is meant is several nature-based tourism objects, including: Beach, Waves, Sand, Merese Hill and Batu Kotak Hill, Sunrise and Sunset, and also the Landscape. Tourism potential the culture they have is the Bau Nyale Tradition. While the tourism potential the artificial means in question are several types of water sport activities such as Surfing, Kitesurf, Stand Up Paddle, Banana Boat, Foil Surf, and Jet Ski. Then, the role of stakeholders in the development of water sports on Tanjung Aan Beach is that the community has played an active role while the government and business actors are still constrained by existing regulations as well as the media and academics (tourism) is still not directly involved in activities and development water sport tourism at Tanjung Aan Beach. Finally, alternative methods for developing water sports at Tanjung Aan Beach is in terms of tourism product development, provision of tourism support facilities, development of promotions based on information and communication technology, development of human resources, and cooperation in marketing of tourism products with various parties. Keywords: tourism; development; water sport; Tanjung Aan Beach